2015
DOI: 10.1016/j.pmedr.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Built environment associations with adiposity parameters among overweight and obese Hispanic youth

Abstract: ObjectiveThe purpose of this cross-sectional study was to establish neighborhood built environment correlates of adiposity as measured by dual X-ray absorptiometry. The utility and methodological gains of using this measure for built environment research were further investigated by comparing model fit across parallel models on body mass index z-scores and waist circumference.MethodsPre-existing data collected from 2001 to 2011 on 576 overweight and obese Hispanic youth were compiled with built environment dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
0
18
0
3
Order By: Relevance
“…Despite the strengths of this study, we did not have diet and physical activity measures or lifetime residential history information. Therefore, results have the potential for residual confounding by poor diet and/or lack of physical activity because each of these factors are associated with increased adiposity, metabolic dysregulation and residential proximity to sources of AAP and TRAP . However, our results are unlikely to be explained by residual confounding by these factors because adjustment for social position, a strong determinant of these factors, did not substantially change our results.…”
Section: Discussionmentioning
confidence: 65%
“…Despite the strengths of this study, we did not have diet and physical activity measures or lifetime residential history information. Therefore, results have the potential for residual confounding by poor diet and/or lack of physical activity because each of these factors are associated with increased adiposity, metabolic dysregulation and residential proximity to sources of AAP and TRAP . However, our results are unlikely to be explained by residual confounding by these factors because adjustment for social position, a strong determinant of these factors, did not substantially change our results.…”
Section: Discussionmentioning
confidence: 65%
“…enrolled 1,720 adults in 2009 and 2010, and it was observed that the BMI of women living in environments where educational levels were lower was 1.12 kg/m 2 higher than the same index among female residents of areas with high educational levels (P < 0.05). Since the schoolchildren of our sample who were from low-income families had less-educated parents ( Table 1), it is reasonable to assume that Concerning the proximity of homes to parks/playgrounds and the association of this factor with both outcomes in the low-income family stratum, Hsieh et al 36 assessed Hispanic girls in Los Angeles, United States, who would be expected to have lower incomes than non-Hispanic residents. They found that the level of body fat was 1.4% lower among those who lived in neighborhoods with more than three acres of space reserved for parks.…”
Section: Resultsmentioning
confidence: 99%
“…Some research shows that the association between access to physical activity facilities and physical activity is stronger for blacks than for whites [84]. Among Hispanics, access to parks is negatively associated with body mass, although that association only holds for girls [85]. Built environment variables are usually more weakly associated with obesity than are individual-level variables [86].…”
Section: Mechanisms and Potential Interventionsmentioning
confidence: 99%